Everyday life in focus in residential child care - Helle Schjellerup Nielsen (Scottish Journal of Residential Child Care)
This paper is based on a study of relationships within a community-based residential establishment in Denmark. The residential unit involved in the study receives children from 4 -17 years, though the average age is 14. Admission on an emergency basis is possible and often used. However, most children are in long-term care (1-2 years) and a few of them for the rest of their childhood. The unit has two sections, each with six children. The sections work separately, but they are within the same house, connected by a corridor and they share playgrounds, meeting rooms and office facilities. Eleven young people were interviewed. Two of the young people, aged 14 and over, still lived in the residential unit, while the rest of the interviewees had moved out of residential care and lived independently. All the statements included in this paper are from the latter group. The study was conducted in cooperation with Karen Zobbe and published in Schjellerup Nielsen & Zobbe (2003).